2013
DOI: 10.1021/cn300198q
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Free Energy Landscapes of the Wild-Type and A30P Mutant-Type α-Synuclein Proteins with Dynamics

Abstract: The genetic missense A30P mutation of the wild-type α-synuclein protein results in the replacement of the 30th amino acid residue from alanine (Ala) to proline (Pro) and was initially found in the members of a German family who developed Parkinson's disease. Even though the structures of these proteins have been measured before, detailed understanding about the structures and their relationships with free energy landscapes is lacking, which is of interest to provide insights into the pathogenic mechanism of Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 63 publications
2
48
0
Order By: Relevance
“…The stability of secondary structure transitions between two specific secondary structure components per residue for the wild-type (WT) and A53T mutant-type (A53T) αS proteins based on free energy calculations performed using our recently developed theoretical strategy. 44,46 The color scale corresponds to the free energy value associated with the specific secondary structure transition between two secondary structure components for a specific residue. that the intramolecular interactions of the C-terminal region with the N-terminal or NAC regions almost disappear upon A53T mutation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The stability of secondary structure transitions between two specific secondary structure components per residue for the wild-type (WT) and A53T mutant-type (A53T) αS proteins based on free energy calculations performed using our recently developed theoretical strategy. 44,46 The color scale corresponds to the free energy value associated with the specific secondary structure transition between two secondary structure components for a specific residue. that the intramolecular interactions of the C-terminal region with the N-terminal or NAC regions almost disappear upon A53T mutation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The differences observed both experimentally and computationally between the different distance-range sensitivities may have implications for aggregation of this protein. Much previous work has attempted to discover the preamyloid or aggregation-prone structure with little success (51)(52)(53)(54)(55). We have previously shown that aggregation of aS is correlated with the intramolecular diffusion coefficient, as measured by Trp-Cys quenching, compared to bimolecular diffusion (19,(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…Coskuner and co-workers studied the structure of the WT αS and the impacts of A53T, E46K and A30P pathological missense mutations on the structure of this protein [ 199 , 200 , 201 ]. IDPs can adopt a multitude of different conformations.…”
Section: Artificial and Pathological Mutations In α-Synuclein: Insmentioning
confidence: 99%